Burden of exposure to infectious bursal disease virus, infectious bronchitis virus, Newcastle disease virus, Mycoplasma gallisepticum, and intestinal parasites in introduced broiler chickens on the Galapagos - Whitehead, Ashley B. R. (PLoS One, 2018)
Diseases in introduced broilers can possibly spill over to wild birds on the Galapagos. Knowledge about the current burden of exposure to pathogens in broilers on the Galapagos is very limited. The objective of the study reported here was to measure the burden of exposure to infectious bursal disease virus (IBDV), infectious bronchitis virus (IBV), Newcastle disease virus (NDV), Mycoplasma gallisepticum (MG), and intestinal parasites in a sample of broiler chickens on 13 farms on Santa Cruz Island and San Cristobal Island in July 2017. Blood serum samples were tested for detection of antibodies to IBDV, IBV, NDV, and MG by using an IDEXX Enzyme-linked Immunosorbent Assay. In addition, fecal samples and pen bedding environmental samples were processed and analyzed for diagnosis of intestinal parasite eggs under a compound light microscope. The frequency of seropositive broilers to IBDV was 74/130 or 56% (95% CI = 48, 65%), to IBV was 27/130 or 20% (14, 28%), and to NDV was 1/130 or 0.7% (0.1, 4%). All broilers tested negative to MG antibodies. Eimeria spp. infection was common in study broilers. Finally, we observed interaction between broiler chickens and wild birds (finches) inside broiler pens, as well as the presence of backyard chickens inside property limits of study farms. This study produced evidence that exposure to IBDV, IBV, and intestinal parasites in broilers on Santa Cruz Island and San Cristobal Island is important. Study results are relevant because (i) they provide new baseline data on the burden of exposure to avian pathogens in broiler farms, (ii) justify the need to verify standard operating procedures in hatcheries that supply (non-vaccinated) day-old chicks to the Galapagos and (iii) to implement enhanced biosecurity standards on broiler chicken farms to mitigate risk of disease transmission between broilers, backyard poultry, and wild birds on the Galapagos.